Sodium- and energy-dependent uptake of myo-inositol by rabbit peripheral nerve. Competitive inhibition by glucose and lack of an insulin effect. - Greene, D A (1982)
Experimental diabetes consistently reduces the concentration of free myo-inositol in peripheral nerve, which usually exceeds that of plasma by 90-100-fold. This phenomenon has been explicitly linked to the impairment of nerve conduction in the acutely diabetic streptozocin-treated rat. However, the mechanism by which acute experimental diabetes lowers nerve myo-inositol content and presumably alters nerve myo-inositol content and presumably alters nerve myo-inositol metabolism is unknown. Therefore, the effects of insulin and elevated medium glucose concentration of 2-[3H]myo-inositol uptake were studied in a metabolically-defined in vitro peripheral nerve tissue preparation derived from rabbit sciatic nerve, whose free myo-inositol content is reduced by experimental diabetes. The results demonstrate that myo-inositol uptake occurs by at least two distinct transport systems in the normal endoneurial preparation. A sodium- and energy-dependent saturable transport system is responsible for at least 94% of the measured uptake at medium myo-inositol concentrations approximating that present in plasma. This carrier-mediated transport system has a high affinity for myo-inositol (Kt = 63 microM), and is not influenced acutely by physiological concentrations of insulin; it is, however, inhibited by hyperglycemic concentrations of glucose added to the incubation medium in a primarily competitive fashion. Thus, competitive inhibition of peripheral nerve myo-inositol uptake by glucose may constitute a mechanism by which diabetes produces physiologically significant alterations in peripheral nerve myo-inositol metabolism.